Hubungan pasar Indonesia dan AS dalam isu inflasi global - Najwa Syaqra Cahyani Bahi (Yayasan Widyantara Nawasena Raharja, 2023)
The downward trend in US inflation tends to have a certain impact on market conditions in Indonesia. The purpose of this study is to examine the impact of the market index in the US on the market index in Indonesia during the phenomenon of declining inflation in the US. This study uses data from the observation period 1 December 2022 to 1 March 2023 as the sample and uses simple linear regression for hypothesis testing. This study finds that the pattern of the market index in Indonesia tends to decrease during the observation period. In addition, this study also finds that the market index in the US tends to have a positive and significant impact on the market index in Indonesia. This finding implies that the decline in inflation in the US tends to result in a positive interaction between the two markets.